Sadomasochism In E.L James' Fifty Shades Trilogy (2011-2012): A Psychoanalytic Approach - Permatasari, Intan, Dr. M. Thoyibi, MS, Nur Hidayat, M.Pd (2016)
This study is about Sadomasochism in E.L James' Fifty Shades Trilogy (2011-2012) which is analyzed using sychoanalytic Approach proposed by Sigmund Freud. The objectives of this study are to find out what sexual acts are committed by the two major characters as practitioners of sadomasochism, to know the response of the partner, and to find out why the author of the trilogy, E.L James xposed sadomasochism in her books. This research is a qualitative research. The primary data of this research is Fifty Shades Trilogy including Fifty Shades of Grey (2011), Fifty Shades Darker (2011), and Fifty Shades Freed (2012). The secondary data of this research are other sources related to the study including websites and books. The researcher draws three conclusions in this research. Firstly, there are three kinds of sexual activities done by the two major characters namely sexual activities without involving tools, sexual activities involving tools, and sexual activities in the playroom. Secondly, there are four kinds of responses shows by the partner namely wanting, enjoying, feeling reluctant, and unbearable. Thirdly, E.L James exposed sadomasochism in her books to illustrate changes in the characters and to show the readers the effects that Christian's childhood has caused.